Analisis Perencanaan Supply Chain Management (SCM) Pada Produksi Minuman Sari Buah UKM Larasati - Urnika Mudhifatul Jannah; Zurriat Nyndia Rahmawati (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2020)
Supply chain management is a concept that discusses the flow of good, cash, and information on an ongoing basis to help the process of business development. One of the business sectors that support the regional economy is Small and Medium Enterprises (SME, or called as UKM in Indonesia). Today, SME is expected to have added value to compete, in terms of showing their existence in regional market. This situation is also faced by SME managed by a women farmer group named Kelompok Wanita Tani (KWT) Larasati located in Palaan village, Ngajum district. KWT Larasati manages production of cup juice. This research aimed to analyze the supply chain management in juice production of KWT Larasati, as well as to overcome the problem in risk management and added value in supply chain of juice production by KWT Larasati in Palaan Village. The research data were collected by interview, observation, questionnaire, and literature study. The respondents of the questionnaire involved 30 members of KWT Larasati. This research result showed the identification of supply chain management and the solution for supply chain management that was integrated with the elements of selecting supplier, logistic planning, production process, and supply distribution.